Linguistic and cultural Barriers in Translating English Idioms into Arabic - Mohammed, Jewayria Mohammed Daffa- Allah (Journal of Ecohumanism, 2025)
Language is the cornerstone of human interaction. It is a tool used to express thoughts, feelings, and ideas. It includes unique nuances, idioms, and slang specific to different regions and cultures. These elements add richness and depth to communication but pose challenges and problems in translation. Translation is the process of rendering aspects and features of a target text semantically, culturally and pragmatically into another language. However, translating idiomatic and culturally-bound expressions has been a challenge for translators as they are culture-bound and involve many cultural elements. The study aims to explore the problems faced by undergraduate students, studying English as FL, while translating English idioms into Arabic. To achieve the main aim of the study, ten English idioms were administered to 40 undergraduate students, randomly chosen, to be translated to Arabic. The analytical descriptive approach was used to check and analyze students’ translations. Results showed that the linguistic and cultural factors are the main causes of students facing problems and encountering barriers in translating English idioms into Arabic. Cultural differences play a vital role in idioms translation. The study targeted the recommendations for solving such problems to courses designers, the instructors of translation course, and the students. Course designers have to include English cultural expressions in the English language courses. Instructors are recommended to choose authentic texts rich in idioms i.e. ’ texts from media. On the other hand, students to follow the strategic, scientific and recommended steps/methods while translation. Moreover, students should try to find the typical equivalent in meaning and form, or at least the nearest equivalent in meaning. The students can tend to literal translation or paraphrasing as the last option while dealing with idioms translation.